MENGUPAYAKAN PENJAGAAN TIDAK FORMAL MERENTAS GENDER: EMPOWERING INFORMAL CARE GIVERS ACROSS GENDER - Mohd. Suhaimi Mohamad (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2018)
In many traditional societies, women play an important role as informal caregiver. They take care of small children, family members who are disabled, old and frail. They perform their role within the private family sphere without much complaints. However when many women enter labour force outside their family many of them can no longer become family care giver. The seperation between nuclear familes and extended families due to rural urban migration makes older women like mothers and mothers in-law can no longer available to provide help. As an alternative, many urban families opt for domestic help to look after their young children, disabled family members and the elderly. Domestic helpers continue their domestic chores as instructed by the lady of the house an at the same time perform caregiving role. The important issue related to having domestic maid to perform care giving role especially in Muslim family is regarding physical contact. Most of the activities in caregiving roles involves physical contact especially during cleaning patients body, changing their clothes, prepare their bed, feeding them, holding their hands and body for therapy. However Islamic paractice do not allow physical contact like touching between two people who are not close family relations or mahram. Since most of domestic maid who also perform the role as caregiver are women, therefore the issue of empowering men to become caregiver is very important because the needs of male caregivers to care for male patients is increasing. Based onwhat is stated in the Quran and hadith and related documents, this paper will outline the need for informal care in families and communities that need to be addressed, particularly those who are Syariah-compliant. Cases from research in the relevant field will be presented to highlight the issues why men should be encourage to consider role as informal caregivers.Dalam banyak masyarakat tradisional, perempuan memainkan peran penting sebagai pengasuh informal. Mereka merawat anak-anak kecil, anggota keluarga yang cacat, tua dan lemah. Mereka melakukan peran mereka dalam ruang keluarga pribadi tanpa banyak keluhan. Namun ketika banyak perempuan memasuki angkatan kerja di luar keluarga mereka, banyak dari mereka tidak bisa lagi menjadi pemberi perawatan keluarga. Pemisahan antara keluarga inti nuklir dan keluarga besar karena migrasi perkotaan pedesaan membuat perempuan yang lebih tua seperti ibu dan ibu mertua tidak lagi dapat menyediakan bantuan. Sebagai alternatif, banyak keluarga perkotaan memilih bantuan rumah tangga untuk menjaga anak-anak mereka, anggota keluarga yang cacat dan orang tua. Pembantu rumah tangga melanjutkan pekerjaan rumah tangga mereka seperti yang diperintahkan oleh nyonya rumah dan pada saat yang sama melakukan peran pengasuhan. Masalah penting terkait dengan memiliki pembantu rumah tangga untuk melakukan peran memberi perawatan terutama dalam keluarga Muslim adalah tentang kontak fisik. Sebagian besar kegiatan dalam peran pengasuhan melibatkan kontak fisik terutama selama membersihkan tubuh pasien, mengganti pakaian, menyiapkan tempat tidur, memberi makan, memegang tangan dan tubuh untuk terapi. Namun paraktek Islam tidak mengizinkan kontak fisik seperti menyentuh antara dua orang yang tidak memiliki hubungan keluarga atau mahram. Karena sebagian besar pembantu rumah tangga yang juga berperan sebagai pengasuh adalah perempuan, maka masalah pemberdayaan laki-laki untuk menjadi pengasuh sangat penting karena kebutuhan pengasuh laki-laki untuk merawat pasien laki-laki semakin meningkat. Berdasarkan apa yang dinyatakan dalam Al-Quran dan hadits dan dokumen terkait, makalah ini akan menguraikan kebutuhan untuk perawatan informal dalam keluarga dan masyarakat yang perlu ditangani, terutama mereka yang mematuhi Syariah. Kasus-kasus dari penelitian di bidang yang relevan akan disajikan untuk menyoroti masalah mengapa laki-laki harus didorong untuk mempertimbangkan peran sebagai pengasuh informal. Keywords: gender, informal care giver, care giving, family.